Vegetative Propagation of Buchanania lanzan Spreng. Root Cuttings - Singh, Jagdish; Banerjee, S. K.; Francis, Alfred (Indian Forester, 2002)
Buchanania lanzan is considered as difficult to root species, hence rooting trial was conducted using two years old root cuttings of Buchanania lanzan in non-mist propagation chamber. The maximum rooting percent (67.66 ), length of longest root (1.89 mm), and number of leaves (1.32) were recorded with IAA 1600 ppm. The maximum rooting per cent (52.7) was observed in root cuttings having 1.5 - 3.5 mm thickness. However, combined effect of cutting thickness and IAA concentration revealed that cuttings having diameter of 3.6 - 5.5 mm showed maximum rooting percentage with 800 and 1600 ppm IAA